Incidence of immune effector cell-associated neurotoxicity among patients treated with CAR T-cell therapy for hematologic malignancies: systematic review and meta-analysis - Han, Min Woo; Jeong, So Yeong; Suh, Chong Hyun; Park, Hyesun; Guenette, Jeffrey P.; Huang, Raymond Y.; Kim, Kyung Won; Yoon, Dok Hyun (Frontiers in Neurology, 2024)
Objectives We aim to assess the pooled incidence of immune effector cell-associated neurotoxicity syndrome (ICANS) in clinical trials and real-world studies of chimeric antigen receptor (CAR) T-cell therapy for hematologic malignancy and compare the incidences among different agents. Methods The PubMed, Embase, and Web of Science databases were searched for clinical trials and real-world studies. An inverse-variance weighting model was used to calculate pooled incidences and subgroup analyses. Multivariable analysis was conducted using binomial-normal modeling. Results Seventy-five trials comprising 3,184 patients were included. The overall pooled incidence was 26.9% (95% CI, 21.7–32.7%) for all-grade and 10.5% (95% CI, 8.1–13.6%) for high-grade ICANS. In subgroup analysis, cohorts with anti-CD19 drugs had significantly higher ICANS incidences than cohorts with other agents. The multivariable analysis demonstrated higher odds of ICANS in anti-CD19 drug studies for high-grade (OR, 4.6) compared to anti-BCMA drug studies. In 12 real-world studies, studies used axicabtagene ciloleucel with CD28 (54.0% all-grade, 26.4% high-grade) exhibited significantly higher rates of all-grade and high-grade ICANS than studies using tisagenlecleucel with 4-1BB (17.2% all-grade, 6.1% high-grade). Conclusions The overall incidences of ICANS with CAR T-cell therapy were 26.9% for all-grade and 10.5% for high-grade. Compared with other agents, patients with anti-CD19 drugs had a significantly increased risk of developing high-grade ICANS. Therefore, careful monitoring of ICANS should be considered for patients undergoing CAR T-cell therapy.